STUDI NUMERIK: PENGARUH DEBIT INLET TERHADAP KARAKTERISTIK PELELEHAN PARAFFIN WAX PADA TABUNG SILINDER - Fajar Anggara; Henry Carles; Pathur Razi Ansyah (Scientific Journal of Mechanical Engineering Kinematika, 2019)
Latent Heat Thermal Energy Storage (LHTES) is the method to store thermal energy by changing the phase of Phase Change Material (PCM). This method is being developed to store heat loss for increasing energy efficiency. In this paper, the effect of variation flow rate on the melting characteristics PCM was investigated by three-dimensional numerical simulation using ANSYS FLUENT 17. The set-up of this research was carried out on concentrically two cylindrical tubes with diameter outer tube 10 cm and length 60 cm while diameter inner tube 5 cm and length 50 cm. The inner tube is used as a PCM container and the outer tube which has bottom and top hole is used as Heat Transfer Fluid (HTF) circulation. Variation HTF or hot water flowrate was carried out by 4L / min, 8L / min and 12 L / min while the temperature is kept at 75oC, then flowed through bottom hole and out to top hole. From this study it was found that the variation flow rate did not have significant effect on the melting pattern, only the greater flow rate, the smaller melting time. Natural convection is the main role of heat transfer when melting.